STRUCTURAL GEOLOGY AND MINERALOGY OF THE SEMANTAN FORMATION (MIDDLE-UPPER TRIASSIC) AROUND TEMERLOH, PAHANG - MAHAMUD, AHMAD HAFIZUDDIN (2016)
This study is to evaluate the structural geology and mineralogy of three outcrops located around Temerloh, Pahang. Stereographic method had been used to investigate the structural geology of the Semantan Formation around Temerloh. About 29 plane plotted stereonet based on strike/dip measurement of bedding and structural features such as faults, folds and fractures have been generated and interpreted. The direction of the force acting on the reverse faults and folds of the outcrops interpreted from a map generated reflect the compression acting on the Semantan Formation of study area. The indication of a possible anticline between location of opposite dipping direction of outcrops can also support the compression deformation experience by the Semantan Formation around Temerloh. Moreover, the the strike bedding of outcrops is also aligned sub-parallel to the compression of central belt of Peninsular Malaysia Hence, it proves that the the Semantan Formation of study area has same direction of compression as central belt of Peninsular Malaysia.